The Mobile Child Forum: Community-Based Child Marriage Prevention Initiatives and Strategies: Forum Anak Bergerak: Inisiatif dan Strategi Pencegahan Perkawinan Anak Berbasis Komunitas - Mukminto, Eko; Qoiri, Mutmainah Nur; Purnomo, Didik; Wahanisa, Rofi; Syahwal, Syahwal (Faculty of Law, Universitas Pattimura, 2026)
Introduction: Child marriage remains a challenge in Pemalang Regency. Numerous studies have shown that child marriage has significant impacts on children’s health, education, and future, particularly for girls. Purposes of The Devotion: This article aims to develop a community-based strategy for preventing child marriage through the empowerment of the Children’s Forum, grounded in a child rights and gender equality approach. Method of The Devotion: This community service program is designed to enhance public understanding—especially among teenagers—of the negative consequences of child marriage and the importance of fulfilling children’s rights through the Children’s Forum community. The program involves training and interactive discussions, strengthening the capacity of the Children’s Forum as agents of change, and fostering collaboration with local government, community leaders, and other stakeholders. This approach is expected to create a community that is more attentive to children’s rights and gender equality, while also supporting Pemalang Regency’s efforts to maintain and improve its Nindya status as a Child-Friendly Regency. Results Main Findings of the Devotion: The outcomes of this community service initiative will be evaluated through success indicators such as the strengthened role of the Children’s Forum in advocating for children’s issues—particularly the prevention of child marriage—and, subsequently, increased public awareness and a reduction in child marriage cases.